Physical Activity and Lung Cancer Risk in the Context of Exposure to Air Pollution – A Review of Current Evidence - Czapla, Natalia; Wisoky, Wiktor; Ziółkowska, Weronika; Strużyńska, Ewelina; Ignyś, Piotr; Łopińska, Joanna; Majchrzycka, Marta; Graczyk, Martyna; Graczyk, Natalia; Majchrzak, Mateusz (Journal of Education, Health and Sport, 2026)
Introduction. Lung cancer remains one of the leading causes of cancer-related mortality worldwide. While tobacco smoking is the primary risk factor, increasing evidence highlights the role of environmental exposures, particularly air pollution, in lung carcinogenesis. At the same time, regular physical activity is widely recognised as an important protective factor against many chronic diseases, including certain types of cancer. However, physical activity performed in polluted environments may increase the inhalation of harmful pollutants due to elevated ventilation during exercise, which raises questions about the interaction between these two factors. Aim of the study. The aim of this narrative review was to analyse the available scientific evidence regarding the relationship between physical activity and lung cancer risk in the context of exposure to air pollution. Methods. A literature review was conducted using PubMed, Scopus and Web of Science databases. Publications addressing epidemiological evidence, biological mechanisms of lung carcinogenesis related to air pollution, and the physiological effects of physical activity were included. Studies analysing the interaction between physical activity and environmental exposure were also considered. Results. The available evidence indicates that regular physical activity is associated with a reduced risk of lung cancer. Potential mechanisms include reduction of chronic inflammation, improved immune surveillance and increased antioxidant capacity. However, physical activity also leads to increased minute ventilation, which may result in higher inhalation of air pollutants. Most studies suggest that under moderate pollution levels the overall health benefits of physical activity outweigh the potential risks related to increased exposure. In environments with high pollution levels, the protective effect of physical activity may be attenuated.